Rapid Assembly of Magnetoplasmonic Photonic Arrays for Brilliant, Noniridescent, and Stimuli‐Responsive Structural Colors. Issue 17 (28th March 2022) - Tran, Van Tan; Kim, Jeonghyo; Oh, Sangjin; Jeong, Ki‐Jae; Lee, Jaebeom
Abstract: There are usually trade‐offs between maximizing the color saturation and brightness and minimizing the angle‐dependent effect in structural colors. Here, a magnetic field‐induced assembly for the rapid formation of scalable, uniform amorphous photonic arrays (APAs) featuring unique structural colors is demonstrated. The magnetic field plays a fundamental role in photonic film formation, making this assembly technology versatile for developing structural color patterns on arbitrary substrates. The synergistic combination of surface plasmonic resonance of the Ag core and broadband light absorption of high refractive index (RI) Fe3 O4 shell in hybrid magnetoplasmonic nanoparticles (MagPlas NPs) enables breaking the trade‐offs to produce brilliant, noniridescent structural colors with high tunability and responsiveness. These features enable the fabrication of various types of highly sensitive and reliable colorimetric sensors for naked‐eye detection without sophisticated instruments. Furthermore, large‐scale structural color patterns are effortlessly achieved, demonstrating the high potential of the present approach for full‐spectrum displays, active coatings, and rewritable papers. Abstract : A unique colloidal assembly of hybrid magnetoplasmonic nanoparticles is demonstrated by cleverly utilizing magnetic forces and infiltration effect, allowing the rapid formation of scalable and uniform amorphous photonic arrays. The unique color‐producing mechanism of the photonic array leads to macroscopically purer structural colors with high tunability and responsiveness.